2003
DOI: 10.1111/j.0014-3820.2003.tb00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Floral Morphometrics and the Evolution of Sexual Dimorphism in Lycium (Solanaceae)

Abstract: Plants of Lycium californicum, L. exsertum, and L. fremontii produce flowers that are either male-sterile (female) or hermaphroditic, and populations are morphologically gynodioecious. As is commonly found in gynodioecious species, flowers on female plants are smaller than those on hermaphrodites for a number of floral traits. Floral size dimorphism has often been hypothesized to be the result of either a reduction in female flower size that allows reallocation to greater fruit and seed production, or an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 48 publications
1
42
0
1
Order By: Relevance
“…Relatively few empirical studies have focused on polyploidy as a possible cause for transition to a dimorphic sexual system. This trigger of gender dimorphism was proposed in studies of North American Lycium (Miller andVenable 2000, 2002;Miller 2002). Of the approximately eighteen North American species, three (L. exsertum, L. fremontii, and L. californicum) are polyploid (Lewis 1961;Chiang-Cabrera 1981), gender dimorphic (Miller and Venable 2000), and selfcompatible (SC; Miller and Venable 2002).…”
mentioning
confidence: 89%
“…Relatively few empirical studies have focused on polyploidy as a possible cause for transition to a dimorphic sexual system. This trigger of gender dimorphism was proposed in studies of North American Lycium (Miller andVenable 2000, 2002;Miller 2002). Of the approximately eighteen North American species, three (L. exsertum, L. fremontii, and L. californicum) are polyploid (Lewis 1961;Chiang-Cabrera 1981), gender dimorphic (Miller and Venable 2000), and selfcompatible (SC; Miller and Venable 2002).…”
mentioning
confidence: 89%
“…Meagher (1999) assumed the G matrix was constant and used a retrospective simulation to determine how strong selection would have had to be to generate the degree of dimorphism seen in dioecious Silene latifolia. Miller and Venable (2003), in contrast, took a phylogenetic approach when comparing flower size of gynodioecious and hermaphrodite Lycium species. Interestingly, both concluded that dimorphism was the result of evolutionary reduction in flower size in the smaller-flowered morph (males in Silene, Meagher 1999; females in Lycium, Miller and Venable 2003).…”
Section: Constraints On the Evolution Of Sexual Dimorphismmentioning
confidence: 99%
“…Miller and Venable (2003), in contrast, took a phylogenetic approach when comparing flower size of gynodioecious and hermaphrodite Lycium species. Interestingly, both concluded that dimorphism was the result of evolutionary reduction in flower size in the smaller-flowered morph (males in Silene, Meagher 1999; females in Lycium, Miller and Venable 2003). However, neither of these approaches can determine whether the sex morphs are currently at their optimal flower size-this requires information on the selective environment.…”
Section: Constraints On the Evolution Of Sexual Dimorphismmentioning
confidence: 99%
“…Phylogenies are, however, rarely known without error. Different estimates of the phylogenetic tree can return different answers to the comparative question (Miller and Venable, 2003;Ober, 2003;Thompson and Oldroyd, 2004), causing a second source of uncertainty known as 'phylogenetic uncertainty' (Pagel and Lutzoni, 2002;Ronquist, 2004;. In this context, Markov chain Monte Carlo methods offer a formal framework to sample phylogenies according to their posterior probabilities.…”
mentioning
confidence: 99%